Effects of Acceptance-Commitment Therapy and Social Skills Training on Depression of Adolescent Students from Father-Absent Families in Lagos State - Makinde, B. O.; Adeyinka, T. J.; Olusakin, A. M. (NIU Journal of Social Sciences; Vol 7 No 1 (2021): KIU Journal of Social Sciences, Vol. 7 No. 1, March 2021, 2021)
The home provides the initial training for the child and the parents act as models for their children since the process of socialization depends on both parents playing complementary roles in bringing up the child. However, some socialization difficulties are encountered where these models are missing due to death, divorce, separation or abandonment. Adolescents from father absent households manifest a number of internalizing and externalizing problem behaviour, including sadness, depression, delinquency, anxiety, interpersonal difficulties and low self-esteem. Thus, this study investigated the effects of Acceptance-Commitment Therapy (ACT) and Social Skills Training (SST) on depression of adolescent students from father-absent families. The research work was hinged on Relational frame theory (RFT) and Social Learning theory. Quasi-experimental pre-test/ post-test group design was used for the study. The population of the study comprised all Senior Secondary two (SS11) students in Lagos state. Simple random sampling was used to select a sample size of 157 Senior Secondary two students comprising of eighty two (82) males and seventy five (75) females. The instruments used to obtain relevant data for the study were Kessler Psychological Distress Scale (K10), Father-Absence Questionnaire (FAQ) and The depression, anxiety and stress scale (DASS). Two research questions were raised and two research hypotheses were generated to guide the study. The pre-test and post test scores were analysed using Analysis of Covariance (ANCOVA) at 0.05 level of significance. The study revealed that Acceptance-Commitment Therapy and Social Skills Training significantly reduced depression among adolescents from father-absent families. It was also revealed that gender did not have any significant impact on depression of the participants in the experimental groups. In the light of the study`s results, the researchers presented a number of recommendations and proposals the most important of which are:  There should be awareness and enlightenment workshops and campaigns for parents on the effects of father absence on the increasing risk of depression resulting to escalating rate of suicide among adolescents in secondary schools.  The Ministry of education and other stakeholders should provide counselling centers equipped with materials for Acceptance-Commitment Therapy and other psychological therapies used in the treatment of depression as an integral and functional part of primary health care centres. Keywords: Acceptance-Commitment Therapy, depression, Social Skills Training, Adolescent students, father-absent family, gender.